ENVIRONMENTAL RACISM IN CHILE - Meza-Lopehandía, Matías (Revista de Historia Social y de las Mentalidades, 2025)
The work concludes that we are in front of the ris ing of a new type social actor, that it emerge from the contradictions of the neoliberal Chile that link it Ìs vindications to the defense of the territory and the peoples right to t heir self-determination.